2004
DOI: 10.1038/sj.npp.1300406
|View full text |Cite
|
Sign up to set email alerts
|

Total Sleep Deprivation Decreases Immobility In The Forced-Swim Test

Abstract: Sleep deprivation can exert antidepressant effects in humans in less than 24 h, making it the fastest acting antidepressant treatment. However, it is rarely used clinically because the effect disappears once the subject goes back to sleep. An understanding of the neurobiological mechanisms underlying the antidepressant effect of sleep deprivation should help to develop new rapidly acting antidepressant strategies. In the present report, an animal model of depression (the forced-swim test) was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 33 publications
(45 reference statements)
6
20
0
Order By: Relevance
“…When compared with control mice, we observed a decrease in immobility to both SD- and KT-treated mice ( p < .05, t test) (Figure 1B, left) with no significant difference between treated groups. Our results are consistent with those of other studies (30,3739). Interestingly, analyzing the activity in 1-minute bins, we observed that all animal groups gradually become immobile, with the saline group being the most immobile.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…When compared with control mice, we observed a decrease in immobility to both SD- and KT-treated mice ( p < .05, t test) (Figure 1B, left) with no significant difference between treated groups. Our results are consistent with those of other studies (30,3739). Interestingly, analyzing the activity in 1-minute bins, we observed that all animal groups gradually become immobile, with the saline group being the most immobile.…”
Section: Resultssupporting
confidence: 94%
“…Our results showed similar efficacy for SD and KT groups that was significantly different from the saline-treated control group. Antidepressant-like activity on the FST for KT (39,52,53) and SD (30,37) has been previously reported.…”
Section: Discussionmentioning
confidence: 82%
“…One night of TSD in rats decreases immobility in the forced swim test, similar to the actions of antidepressant drugs (Lopez-Rodriguez et al, 2004). Furthermore, like antidepressant treatment, TSD in rats stimulates hippocampal neurogenesis (Grassi Zucconi et al, 2006).…”
Section: Treating Mood Disorders By Altering the Circadian Cycle 41 mentioning
confidence: 89%
“…On the other hand, TSD could increase serotonin concentrations in different areas of the brain including hippocampus (45). Behavioral tests have also shown the antidepressant effects of TSD in animal models (46). The antidepressant effect of SD is, however, not believed to be related to the associated anxiolytic-like process (47).…”
Section: Discussionmentioning
confidence: 99%